Lithium isotope fractionation during magmatic differentiation and hydrothermal processes in rare-metal granites. (1st November 2018) - Li, Jie; Huang, Xiao-Long; Wei, Gang-Jian; Liu, Ying; Ma, Jin-Long; Han, Li; He, Peng-Li
Abstract: Lithium isotope composition is potentially an effective geochemical tracer for hydrothermal processes and magmatic differentiation associated with rare-metal granitic rocks. The Yashan and Xihuashan plutons in South China are extraordinarily Li-F rich rare-metal granites that contain niobium-tantalum and tungsten deposits, respectively. As a moderately incompatible trace element in a felsic melt system, Li notably increases from protolithionite granite and Li-mica granite (88.7–175 μg/g) to topaz-lepidolite granite (7430–8080 μg/g) in the Yanshan pluton. Despite a large variation in Li concentrations, the δ 7 Li values of the Yashan pluton vary within in a narrow range from −1.5‰ to 1.5‰. In contrast, the δ 7 Li values of the Xihuashan pluton notably increase from biotite granite and two-mica granite (−0.2‰ to +0.7‰) to muscovite granite (+1.9‰ to +4.4‰) with much less variation in the Li concentrations (37.8–209 μg/g), which is best explained by the high diffusion rate of 6 Li relative to 7 Li during disequilibrium fluid-rock interaction. The Xihuashan greisen has negative δ 7 Li values (from −2.7‰ to −2.1‰), which are attributed to extensive fluid-rock interaction in an open system. Lithium isotope fractionations are consistent with a diversity of mineralization in the rare-metal granitic rocks. Tungsten mineralization is likely associated with an open hydrothermal process. Fluid-rock interaction has a much stronger effect on Li isotope fractionation than does magmatic differentiation in a highly evolved magmatic system. Ta-Nb mineralization is related to the magmatic differentiation in a closed magmatic-hydrothermal system. The exsolution of a supercritical fluid during magmatic differentiation and fluid-rock interaction in a closed magmatic-hydrothermal system is insufficient for producing notable Li isotope fractionation.